2015
DOI: 10.1097/sap.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Paramedian Forehead Flap in 2 Stages (87 Flaps) and 3 Stages (100 Flaps)

Abstract: To our knowledge, our study is the largest series published to date and the first one to compare the prevalence of forehead flap necrosis in the 2- versus the 3-stage technique for paramedian forehead flaps. We found no evidence that the use of a 3-stage forehead flap lowers the prevalence of necrosis. Until larger multicenter studies or meta-analyses can be conducted, smaller yet well-conducted studies such as the present one provide critical data and represent an important contribution to the field. Future r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…If the defects are not closed, contractures or large scar formations may occur due to secondary healing or use of skin grafts [ 14 ]. Santos Stahl et al [ 15 ] and Little et al [ 16 ] reported an approximately 5% increase in the rate of skin necrosis after a forehead flap. Skin necrosis was however not noted in any of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…If the defects are not closed, contractures or large scar formations may occur due to secondary healing or use of skin grafts [ 14 ]. Santos Stahl et al [ 15 ] and Little et al [ 16 ] reported an approximately 5% increase in the rate of skin necrosis after a forehead flap. Skin necrosis was however not noted in any of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Paramedian forehead flaps can be performed in two or three stages according to the surgeon experience and patient’s condition ( 9 , 10 ). In our study, the operations were done in two or three sessions.…”
Section: Discussionmentioning
confidence: 99%
“…The paramedian forehead flap is one of the most widely used flaps for full thickness reconstruction of nasal defects and is considered the gold standard for nasal reconstruction. 1 , 2 Although this technique is known for its viability in patients of all ages, having few contraindications, producing reliable and aesthetically pleasing results, 3 as well as achieving high rates of patient satisfaction and having low complication rates, 4 , 5 the paramedian forehead flap procedure has one major drawback, namely that it is a two‐stage surgery design. Traditionally, the paramedian forehead flap is transferred in two stages: stage 1 involves raising the flap and reconstructing the nasal tissues according to the nasal subunit principles, while leaving a pedicle to the donor site.…”
Section: Introductionmentioning
confidence: 99%